Turner Center for the Arts Box 1 Folder 24 - Turner Center for the Arts (Valdosta State University Archives and Special Collections, 2003)
Turner Center for the Arts, Scrapbook Box 1 Folder 24, 2003
1 electronic records, PDF/A, PDF. Includes 101 page scans, XXX bytes
Keywords: Scrapbook; Clippings (Books, newspapers, etc.); Valdosta (Ga.); arts and community